Effectiveness of Virtual Reality-Based Badminton Simulating In-Game Scenarios on Students' Badminton Performance - Sri Wicahyani; Abdul Rachman Syam Tuasika; Sapto Wibowo; Mochamad Ridwan; Supriyono Supriyono; Diva Ristie Valentina; Muchammad Arif Krisna Wijaya; Alvin Afandi; Nandya Rizky Nur Febriana (International Journal of Educational Evaluation and Policy Analysis, 2026)
Badminton instruction in higher education is commonly dominated by isolated technical drills, limiting students' ability to transfer acquired skills into authentic match situations that require tactical awareness and rapid decision-making. This study aimed to develop and evaluate the effectiveness of a Virtual Reality (VR)-Based Badminton Simulating In-Game Scenarios learning model for improving university students' badminton performance. A Research and Development (R&D) approach employing the ADDIE instructional design model was adopted, comprising the phases of analysis, design, development, implementation, and evaluation. The developed VR application was implemented with 24 undergraduate students enrolled in a badminton course using a one-group pre-test–post-test design. Data were collected through expert validation, badminton skill assessment, observation, and student response questionnaires. The normality of the data was examined using the Shapiro–Wilk test, while differences between pre-test and post-test scores were analyzed using the Wilcoxon Signed-Rank Test. The results demonstrated statistically significant improvements in player performance (Z = –2.718, p = 0.007) and match-winning performance (Z = –3.051, p = 0.002) following the VR intervention. These findings indicate that the developed learning model effectively enhances badminton performance by providing immersive and representative learning environments that integrate technical execution, tactical awareness, perception–action coupling, and contextual decision-making. This study contributes to technology-enhanced sport education by proposing an innovative VR-based instructional model that extends conventional badminton learning beyond isolated technical practice toward authentic game-based learning experiences.